2010
DOI: 10.1021/jp1031702
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Structural Study of the Crystal Phases and Mesophases in the Lithium and Thallium(I) Propanoates and Pentanoates Binary Systems: Formation of Mixed Salts and Stabilization of the Ionic Liquid Crystal Phase

Abstract: The temperature and enthalpy vs composition phase diagrams of the binary systems [xC(2)H(5)CO(2)Li + (1 - x)C(2)H(5)CO(2)Tl], and [x(n-C(4)H(9)CO(2)Li) + (1 - x)n-C(4)H(9)CO(2)Tl], where x is the mole fraction, were determined by DSC. Both binary systems display the formation of one 2:1 mixed salt each (at x = 0.667) that appear as a peritectic (incongruent melting) at T(fus) = 512.0 K, and T(fus) = 461.1 K, with Delta(fus)H(m) = 13.76 and 8.08 kJ.mol(-1) for Li-Tl (I) propanoates, and n-pentanoate mixed salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 73 publications
1
30
1
Order By: Relevance
“…It has been observed that due to a smectic anisotropic molecular arrangement, electric current conductivity along the cation-anion layers is larger by four orders of magnitude than that in the perpendicular direction. Tl pentanoate ( A , M m+ = Tl + , (Z − ) = -COO − , Scheme 17) exhibits a smectic mesophase in a range of 180–214 °C, which could be stabilized by the addition of Li pentanoate [105]. Long-chain Eu alkanoates ( A , (Z − ) = -COO − , n = 6–9, Scheme 17) display lamellar structures, where Eu ionic layers are separated by perpendicularly oriented alkanoate chains arranged in a hexagonal packing [106].…”
Section: Metallomesogensmentioning
confidence: 99%
“…It has been observed that due to a smectic anisotropic molecular arrangement, electric current conductivity along the cation-anion layers is larger by four orders of magnitude than that in the perpendicular direction. Tl pentanoate ( A , M m+ = Tl + , (Z − ) = -COO − , Scheme 17) exhibits a smectic mesophase in a range of 180–214 °C, which could be stabilized by the addition of Li pentanoate [105]. Long-chain Eu alkanoates ( A , (Z − ) = -COO − , n = 6–9, Scheme 17) display lamellar structures, where Eu ionic layers are separated by perpendicularly oriented alkanoate chains arranged in a hexagonal packing [106].…”
Section: Metallomesogensmentioning
confidence: 99%
“…[34][35][36] Reports on tetrahalidometalate-based ILCs and their transformation into inorganic materials are, however, relatively rare. [30][31][32][33][37][38][39][40][41][42][43][44][45][46][47] This is somewhat surprising because metal containing ILs and ILCs may open the door towards a new valuable branch of IL research, which derives its importance from the additional properties such as colour, geometry, or magnetism, which are brought about the material by the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the systems between lithium and thallium(I) propionates and pentanoates have been recently analyzed in depth by our group. 18 Pure lithium and thallium(I) butyrates have been studied separately by different calorimetric techniques, such as adiabatic calorimetry, 19,20 DSC, 21,22 and TG. 23,24 However, the crystal structure of alkanoates belonging to the respective series were solved in the last 2 years, for example LiC4, 25 LiC3 and LiC5, 26 anhydrous LiC2 and hydrates, 27 or TlC3.…”
Section: Introductionmentioning
confidence: 99%